Reactive and 'clickable' hydrophilic nanofibers as novel biomaterials - Kalaoğlu Altan, Özlem İpek. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
Among many other nanomaterials, polymeric nanofibers have gained attraction in biomedical applications due to their unique properties such as high surface area, porosity and physical resemblance to the extracellular matrix. Electrospinning is the most commonly used method for producing nanofibers due to its low-cost, simplicity and efficiency. These nanofibers usually need to be modified with a biological material for bioapplications in order to enhance their biocompatibility, cell-adhesivity and stimuli-responsivity. Recently, ‘click’ chemistry, in particular metal-free click reactions, has emerged as a preferred method for the functionalization of electrospun nanofibers as it enables efficient and orthogonal functionalization under mild reaction conditions. In this thesis, clickable polymers with various reactive groups were designed and electrospun into reactive nanofibers which were aimed to be used for the reagent-free (bio)functionalization of nanofibers under mild reaction conditions. In the first project, furan-bearing acrylate-based non-biodegradable nanofibers were produced and modified with maleimide-containing fluorescent dye and biotin ligand via Diels-Alder reaction. In the second project, maleimide-containing acrylate-based non-biodegradable nanofibers were obtained and photo-patterned. The patterned nanofibers were biofunctionalized with a thiol-bearing oligonucleotide via Michael reaction, followed with hybridization with its complementary sequence. The third project involved the in situ crosslinking of polyoxazoline-based nanofibers. The alkene unit on the polymer was used for modification of the crosslinked nanofibers via thiol-ene reaction. In the fourth project, furan-bearing biodegradable polylactide nanofibers were produced and modified with a maleimide-containing RGD peptide via Diels-Alder reaction, followed by cell culture on the modified nanofibers. In the last project, dual-functional biodegradable polylactide nanofibers were obtained and modified with fluorescent dyes and biomolecules using strain-promoted azide-alkyne cycloaddition and inverse electron-demand Diels-Alder reaction.
Keywords: Nanofibers.; Biomedical materials.